2017
DOI: 10.1007/s00204-017-2130-7
|View full text |Cite
|
Sign up to set email alerts
|

Planarian cholinesterase: molecular and functional characterization of an evolutionarily ancient enzyme to study organophosphorus pesticide toxicity

Abstract: The asexual freshwater planarian Dugesia japonica has emerged as a medium-throughput alternative animal model for neurotoxicology. We have previously shown that D. japonica are sensitive to organophosphorus pesticides (OPs) and characterized the in vitro inhibition profile of planarian cholinesterase (DjChE) activity using irreversible and reversible inhibitors. We found that DjChE has intermediate features of acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). Here, we identify two candidate genes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 76 publications
1
56
0
1
Order By: Relevance
“…The mean displacement for 238 every 30 second bin was then calculated. We previously found that under similar, low-throughput 239 conditions, wild-type D. japonica exposed to noxious heat exhibit frequent turns and decreased 240 movement followed by eventual paralysis (Hagstrom et al, 2018). Thus, the assay was separated 241 into phases: 1) the initial dynamic reaction and 2) the persistent decreased movement once the 242 reaction stabilized ( Supplementary Figure 1).…”
Section: Screening Platform: 211mentioning
confidence: 97%
See 4 more Smart Citations
“…The mean displacement for 238 every 30 second bin was then calculated. We previously found that under similar, low-throughput 239 conditions, wild-type D. japonica exposed to noxious heat exhibit frequent turns and decreased 240 movement followed by eventual paralysis (Hagstrom et al, 2018). Thus, the assay was separated 241 into phases: 1) the initial dynamic reaction and 2) the persistent decreased movement once the 242 reaction stabilized ( Supplementary Figure 1).…”
Section: Screening Platform: 211mentioning
confidence: 97%
“…Experimental 166 concentrations were made using 2-fold serial dilutions in IO water. D-sorbitol (D-glucitol) served 167 as a negative control (Zhang et al, 2018) and was prepared using serial half-log dilutions in IO 168 water. All dilutions were made and used fresh on Day 1 of the assay.…”
Section: Specimen: 146mentioning
confidence: 99%
See 3 more Smart Citations